Cardiopulmonary Exercise Capacity and Preoperative Markers of Inflammation - Pervez Sultan; Mark R. Edwards; Ana Gutierrez del Arroyo; David Cain; J. Robert Sneyd; Richard Struthers; Gary Minto; Gareth L. Ackland (Mediators of Inflammation)
Explanatory mechanisms for the association between poor exercise capacity and infections following surgery are underexplored. We hypothesized that aerobic fitness—assessed by cardiopulmonary exercise testing (CPET)—would be associated with circulating inflammatory markers, as quantified by the neutrophil-lymphocyte ratio (NLR) and monocyte subsets. The association between cardiopulmonary reserve and inflammation was tested by multivariable regression analysis with covariates including anaerobic threshold (AT) and malignancy. In a first cohort of 240 colorectal patients, AT was identified as the sole factor associated with higher NLR (P=0.03) and absolute and relative lymphopenia (P=0.01). Preoperative leukocyte subsets and monocyte CD14+ expression (downregulated by endotoxin and indicative of chronic inflammation) were also assessed in two further cohorts of age-matched elective gastrointestinal and orthopaedic surgical patients. Monocyte CD14+ expression was lower in gastrointestinal patients (n=43) compared to age-matched orthopaedic patients (n=31). The circulating CD14+CD16− monocyte subset was reduced in patients with low cardiopulmonary reserve. Poor exercise capacity in patients without a diagnosis of heart failure is independently associated with markers of inflammation. These observations suggest that preoperative inflammation associated with impaired cardiorespiratory performance may contribute to the pathophysiology of postoperative outcome.